THE IMPLEMENTATION OF PICTURE SERIES IN TEACHING WRITING PROCEDURAL TEXT AT TENTH GRADE OF SMAN 1 SAKRA IN ACADEMIC YEAR 2022/2023 - Zidni Hidayatul Fitri; Santi Farmasari; Atri Dewi Aziz (Journal of English Education Forum (JEEF), 2022)
This study intended to determine whether the use of picture series is effective in teaching writing procedural text and which components of writing increase after the use of picture series in teaching writing procedural text at the tenth grade of SMAN 1 Sakra. The research method was quasi-experimental with a control group pretest and post-test design. The population was tenth-grade students. The sample was 50 students from 2 classes, 10 E was the experimental group, and then 10 J was the control group. Samples were taken using random cluster sampling. The instrument of data collection was a written test. The result of the t-test was 3.953, and the t-table was 2.011 for df 48 (50-2) at a significant level of 0,05 (95%). It can be concluded that H0 was rejected and Ha was accepted. Thus, the use of picture series was effective in teaching writing procedural text in the tenth grade of SMAN 1 Sakra. While, the components of writing in the experimental group which increased overall after using picture series in writing procedural text were content, organization, and grammar.